Publisher Correction: Understanding dynamic friction through spontaneously evolving laboratory earthquakes - V. Rubino (Nature Portfolio, 2019)
The HTML version of this Article incorrectly omits Supplementary Movie 1. Supplementary Movie 1 can be found as Supplementary Information associated with this Correction.